Portaria PRR5 nº 106, de 10 de junho de 2019 - Marcelo Alves Dias de Souza (DOU, Brasília, DF, 13 jun. 2019, Seção 2, p 54., 2019)
Exonera e nomeia bacharéis em Direito para exercer cargo em comissão.